2017
DOI: 10.18632/oncotarget.15007
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptors agonist GW3965 re-sensitizes gefitinib-resistant human non-small cell lung cancer cell to gefitinib treatment by inhibiting NF-κB in vitro

Abstract: The recent research shows that the inhibition of the nuclear factor-κB (NF-κB) pathway is a promising therapeutic option for patients who progress after treatment with the novel mutant-selective EGFR-TKIs. For propose to find a nontoxic drug to reverse the acquired gefitinib resistance, we examined whether the Liver X Receptors agonist GW3965 affect gefitinib resistance of HCC827/GR-8-2 cells. Cell viability was measured by CCK-8 assay. Levels of NF-κB, p-AKT and caspases were detected by Western blot analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…Moreover, in HCC827-GR and PC9-GR cells, we also showed that with PPARγ expression stable, si-LXRα depressed LXRα and ABCA1 expression levels, which approved that LXRα is a downstream target gene of the PPARγ, consistent with previous reports [31]. There was another report that the lung adenocarcinoma cells proliferation could be restrained by LXRα activation [22]. Therefore, cancer cells proliferation may be increased followed by LXRα and ABCA1 inactivated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, in HCC827-GR and PC9-GR cells, we also showed that with PPARγ expression stable, si-LXRα depressed LXRα and ABCA1 expression levels, which approved that LXRα is a downstream target gene of the PPARγ, consistent with previous reports [31]. There was another report that the lung adenocarcinoma cells proliferation could be restrained by LXRα activation [22]. Therefore, cancer cells proliferation may be increased followed by LXRα and ABCA1 inactivated.…”
Section: Discussionsupporting
confidence: 90%
“…In the process of initiation and development of lung adenocarcinoma, the expressions of PPAR, LXR, and ABCA1 were decreasing. On the other hand, the lung adenocarcinoma cells proliferation could be inhibited by the over expression of the three genes above .Our findings that efatutazone elevated the expression of PPAR γ , LXR α , and ABCA1 further proved that efatutazone participates in PPAR γ /LXR α /ABCA1 pathway in HCC827‐GR and PC9‐GR cells.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…miRNAs play critical roles in multiple human cancers, such as colorectal cancer (Liang et al, 2015), gallbladder cancer (Ma et al, 2015), as well as lung cancer (Hu et al, 2017). MiR-513b is a member of miR-513 subfamily, which belongs to an X-linked primate-specific miR506-514 cluster (Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…GW3965 has previously been found to decrease NF-κB transcriptional activity [ 280 ]. The findings of a report have supported that GW3965 could be an effective treatment for gefitinib resistance [ 281 ]. Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature granulocytic and monocytic cells that are important components of the tumor microenvironment (TME).…”
Section: Nrs In Lung Cancermentioning
confidence: 98%